2007
DOI: 10.1002/cne.21478
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and functional profiling of the normal rat retina

Abstract: We established a metabolic and functional profile map of the normal rat retina, given the premise that: 1) amino acid neurochemistry reflects metabolic integrity and cellular identity, and 2) the permeation of a cation channel probe, agmatine (1-amino-4-guanidobutane, AGB), reflects cation channel functionality. The purpose was to provide a unique method of simultaneously assessing the metabolic and functional characteristics of the normal retina, upon which a comparison can be made to disease models. Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
79
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(84 citation statements)
references
References 86 publications
5
79
0
Order By: Relevance
“…His assumption was based on the known location of cholinergic cell somata and distinct bistratified dendritic location in the inner plexiform layer. Subsequent development of techniques to combine AGB and macromolecular markers (Marc et al, 2005) confirmed that Marc's linking proposition was indeed correct (Sun et al, 2007b). We acknowledge that unless other cell markers are used (e.g., macromolecular markers) or pattern recognition is undertaken, some errors will occur in cell assignment in borders or locations where the cells coexist.…”
Section: Immunocytochemical Analysismentioning
confidence: 68%
See 1 more Smart Citation
“…His assumption was based on the known location of cholinergic cell somata and distinct bistratified dendritic location in the inner plexiform layer. Subsequent development of techniques to combine AGB and macromolecular markers (Marc et al, 2005) confirmed that Marc's linking proposition was indeed correct (Sun et al, 2007b). We acknowledge that unless other cell markers are used (e.g., macromolecular markers) or pattern recognition is undertaken, some errors will occur in cell assignment in borders or locations where the cells coexist.…”
Section: Immunocytochemical Analysismentioning
confidence: 68%
“…Similar to other rodent retinas (Fletcher andKalloniatis, 1996, 1997a,b), the mouse retina displays distinct cellular location during development, identified using pattern recognition of amino acid labeling patterns (Chua, 2008;Kalloniatis et al, 2012). Soma size, dendritic disposition, and labeling intensity are also supportive components in cellular classification (Sun et al, 2007b). The use of all or some of these principles allows the identification of core cell classes, e.g., bipolar cells, amacrine cells, ganglion cells.…”
Section: Immunocytochemical Analysismentioning
confidence: 98%
“…Briefly, a 3-L intravitreal injection of AGB (final vitreal concentration of 10 mM) was administered 30 minutes prior to enucleation. Details of the tissue preparation following enucleation have also been described in Sun et al (2007b). Briefly, tissue was collected Ϸ1-2 mm from the optic nerve head, fixed in 2.5% glutaraldehyde / 1% paraformaldehyde, resin-embedded, and processed for postembedding silver-intensified immunocytochemistry (Kalloniatis and Fletcher, 1993;Marc, 1999a,b;Sun et al, 2003).…”
Section: In Vivo Agb Injection Tissue Preparation and Immunocytochementioning
confidence: 99%
“…Procedures for the in vivo injection of AGB have been previously described (Sun et al, 2007b). Briefly, a 3-L intravitreal injection of AGB (final vitreal concentration of 10 mM) was administered 30 minutes prior to enucleation.…”
Section: In Vivo Agb Injection Tissue Preparation and Immunocytochementioning
confidence: 99%
See 1 more Smart Citation